Anticipatory action and implementation of the IGAD regional roadmap - Otieno, George (IGAD Climate Prediction and Applications Centre, 2025)
Presented at the Jameel Observatory drylands food security and resilience early action research and evidence dialogue, Addis Ababa, Ethiopia, 15-16 May 2025